2006
DOI: 10.1111/j.1600-6143.2005.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Costs of Sepsis and Pneumonia Before and After Renal Transplantation in the United States

Abstract: We compared the graft survival and accumulative costs associated with sepsis and pneumonia pre-and post-transplantation. We analyzed 44 916 first kidney transplants from 1995 to 2001 USRDS where Medicare was the primary payer. We drew five cohorts for each disease from the baseline population: patients who had a disease onset in the first or second years pre-transplantation (cohorts 1 and 2) or post-transplantation (cohorts 3 and 4) and patients who were disease-free (cohort 5). For each cohort, we calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 12 publications
2
54
0
Order By: Relevance
“…Infections not only increased the risk for death with a functioning graft by fivefold, but also increased the risk for death-censored graft failure by twofold. Consistent with these observations, we have previously shown that posttransplant urinary tract infection, whether inpatient or outpatient, was significantly associated with an increased risk of death-censored graft loss, in addition to an increased risk of death, in kidney transplant recipients (8 (14). In the opinion of the authors of the USRDS report, the higher risk for death-censored graft failure after an infection could plausibly result from acute rejection or graft dysfunction causing both infections and death-censored graft failure.…”
Section: Discussionsupporting
confidence: 76%
“…Infections not only increased the risk for death with a functioning graft by fivefold, but also increased the risk for death-censored graft failure by twofold. Consistent with these observations, we have previously shown that posttransplant urinary tract infection, whether inpatient or outpatient, was significantly associated with an increased risk of death-censored graft loss, in addition to an increased risk of death, in kidney transplant recipients (8 (14). In the opinion of the authors of the USRDS report, the higher risk for death-censored graft failure after an infection could plausibly result from acute rejection or graft dysfunction causing both infections and death-censored graft failure.…”
Section: Discussionsupporting
confidence: 76%
“…A multicenter study from the United States Renal Data System calculates the significant additional cost of USD 38,400 for one incidence of pneumonia during the period of 1 year after transplantation [31].…”
Section: Discussionmentioning
confidence: 99%
“…While kidney transplant recipients who have Medicare as their primary insurer may differ systematically from those who use other reimbursement systems, Medicare claims are particularly relevant to research among kidney transplant recipients because, unlike the eligibility requirements of age >65 or disability in the general population, renal allograft recipients are offered disease-specific Medicare entitlement and Medicare is the largest single insurer in this population. As a result, Medicare billing claims have been used to study a variety of complications after kidney transplantation (17, 19, 52, 53). Regarding our costs regression approach, alternatives to our OLS models, such as regressions estimating the determinants of the natural log of Medicare payments, may be more efficient but also may produce biased estimates and are difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Cancers were classified as NMSC, viral-linked, and “other” cancers (SDC 1, Table), per prior categorizations (4, 6, 18). We required 1 inpatient claim or 2 other claims on separate dates to classify a cancer, as performed in previous studies of claims data to identify other serious conditions in the kidney transplant population (3, 4, 17, 19, 20). …”
Section: Methodsmentioning
confidence: 99%